Plan de carrera (2021)
The career plan allows the organization and collaborators to obtain a comprehensive training project, establishing mutual commitments, such as satisfaction of learning needs and continuous professional growth, in turn, they will identify the means you need to achieve the proposed goals. The organization obtains by means of the knowledge of the human resource better positioning in the market in front of its competitors, giving scope to the vision. The objective of the Career Plan is to develop it in the company ISEC S.A, with the support of senior management and leaders in order to optimize the best organizational climate in a great place to work.